miRNAs in Extracellular Vesicles from iPS-Derived Cardiac Progenitor Cells Effectively Reduce Fibrosis and Promote Angiogenesis in Infarcted Heart - Wanling Xuan; Lei Wang; Meifeng Xu; Neal L. Weintraub; Muhammad Ashraf (Stem Cells International)
Cardiac stem cell therapy offers the potential to ameliorate postinfarction remodeling and development of heart failure but requires optimization of cell-based approaches. Cardiac progenitor cells (CPCs) induction by ISX-9, a small molecule possessing antioxidant, prosurvival, and regenerative properties, represents an attractive potential approach for cell-based cardiac regenerative therapy. Here, we report that extracellular vesicles (EV) secreted by ISX-9-induced CPCs (EV-CPCISX-9) faithfully recapitulate the beneficial effects of their parent CPCs with regard to postinfarction remodeling. These EV contain a distinct repertoire of biologically active miRNAs that promoted angiogenesis and proliferation of cardiomyocytes while ameliorating fibrosis in the infarcted heart. Amongst the highly enriched miRNAs, miR-373 was strongly antifibrotic, targeting 2 key fibrogenic genes, GDF-11 and ROCK-2. miR-373 mimic itself was highly efficacious in preventing scar formation in the infarcted myocardium. Together, these novel findings have important implications with regard to prevention of postinfarction remodeling.